Preferences for Nuclear Power in Post-Fukushima Japan: Evidence from a Large Nationwide Household Survey - Toshihiro Okubo; Daiju Narita; Katrin Rehdanz; Carsten Schröder (energies, 2020)
Utilizing the data of a large nationwide household survey conducted in 2014, we investigate public preferences on nuclear power in Japan after the Fukushima nuclear accident and the role of four sets of factors: (1) household/individual socioeconomic characteristics, (2) psychological status, (3) geographical aspects, and (4) Fukushima accident-related experiences. The preferred energy mix, according to the averaged responses from the survey, includes 0.59 for renewables, 0.29 for fossil fuels, and 0.12 for nuclear—much more skewed towards the renewables than the actual national share of renewables of less than 0.2. Male, older, unmarried, less educated, high-income people, and government party supporters have a preference towards a higher share of nuclear power, except if they live near nuclear power plants. The experience of blackout and aversion to nuclear power during the Great East Japan Earthquake of 2011 lowers the share of nuclear power in the preferred mix.
Keywords: 330; Energy mix; Nuclear power plant; Fukushima; Promixity; Household survey